Eksistensi Hukum Tanah Adat Sebagai Pedoman dalam Penggunaan dan Pemanfaatan Tanah Adat oleh Masyarakat Adat Woloara Kabupaten Ende - Maran, Mary Grace Megumi; Geme, Maria Theresia; Lay, Benediktus Peter (Jurnal Ilmiah Global Education, 2025)
This study aims to examine and analyse the existence of Woloara customary land law and to examine and analyse the use and utilisation of land by the Woloara indigenous community based on Woloara customary land law. This study is an empirical legal study using three approaches, namely the legislation approach, legal sociology, and legal history. Based on the research conducted, it is known that Woloara customary land law contains important elements, namely commands, permissions, prohibitions, and sanctions, which are also closely related to respect for Embu Mamo (ancestors) and Nggae (God). In the context of this study, the indicators used to analyse the existence of customary land law, particularly among the Woloara indigenous community, are divided into three main aspects, namely: objects, values, and sustainability. Woloara customary land law is still valid and exists in community life, particularly in the use and utilisation of land. This is marked by the permissions, commands, prohibitions, and sanctions created by the Embu Mamo in ancient times, which are still recognised, obeyed, and enforced in community life. This is also evident from the continued use of the same objects, values that are generally unchanged, and sustainability that has shown that elements of customary land law continue to be applied in land use and utilisation activities. Furthermore, based on the results of the study, it is known that customary land law serves as a guideline in the implementation of land use and utilisation, which results in various types of land use and utilisation, namely land use and utilisation based on subject, land use and utilisation based on land type, land use and utilisation based on area function, land use and utilisation based on type of activity, and land use and utilisation based on social status.